Immune Privilege Furnishes a Niche for Latent Infection - Forrester, John V.; Mölzer, Christine; Kuffova, Lucia (Frontiers in Ophthalmology, 2022)
The microenvironment of the CNS (eye and brain) is fertile ground for infection if the barriers are breached. The result of pathogen invasion is often devastating destruction of tissues. In the eye, inflammation is broadly classified either as "infectious" (ie caused by infection) or "non-infectious". However, increasingly, forms of intraocular inflammation (IOI), which clinically appear to be "non-infectious" turn out to be initiated by infectious agents, suggesting that pathogens have been retained in latent or persistent form within ocular tissues and have reactivated to cause overt disease. A similar pathogenesis applies to latent infections in the brain. Not all CNS tissues provide an equally protective niche while different pathogens escape detection using different strategies. This review summarises how immune privilege (IP) in the CNS may be permissive for latent infection and allow the eye and the brain to act as a reservoir of pathogens which often remain undetected for the lifetime of the host but in states of immune deficiency may be activated to cause sight- and life-threatening inflammation.